Inkulturasi dalam Ritus Perkawinan Katolik di Paroki Santo Thomas More, Maumere - Yohanes Hans Monteiro; Wishal Ambrose (MARSAHALA : Jurnal Studi Agama dan Budaya, 2026)
This study examines the inculturation of the Catholic Rite of Matrimony at St. Thomas More Parish, Maumere, by analyzing the relationship between sacramental integrity, local culture, and pastoral practice. Using a qualitative ethnographic approach, data were collected through participant observation, semi-structured interviews with clergy, parish staff, and engaged couples, and analysis of liturgical and pastoral documents. The findings show that the essential structure of the Rite of Matrimony remains intact, especially the exchange of consent, the blessing and exchange of rings, and the nuptial blessing, while local cultural expressions such as traditional attire, music, language, symbolic gestures, and family participation enrich the celebration and strengthen communal participation. The study also finds that marriage preparation, including the laporan kanonik and final pastoral consultation, functions as a space for catechesis, discernment, and accompaniment. These practices demonstrate that inculturation in this parish is not merely decorative, but pastorally guided and theologically grounded in the Paschal Mystery of Christ. This study contributes to liturgical theology and pastoral praxis by showing how local cultural forms can strengthen ecclesial identity without compromising sacramental integrity.